The role of IT consulting practice: a successful enterprise mobility solution - Fakhri, Nurul Fahimah; Ibrahim, Jamaludin (Research Publish Journals, 2015)
Mobile technologies are progressing to advance and reform the technology landscape promotes a global connectivity where people can access information in a real time from anywhere. This revolution has changed the way business is conducted including Information Technology (IT) consulting organization to reconsider the benefits of mobile technology and inclusive mobility consulting strategies to retain clients and heightened consulting performance. IT consulting field focuses on providing expert advice and assistance on the best use of information technology to meet the business objectives of an organization including writing, modifying, testing and supporting software to meet the customer needs. Whereas, mobile technology refers to mobile applications allows communication or interaction via mobile devices. The advancement of mobile technology in the enterprise market has concerned many companies to face the challenges for their Enterprise mobility. Hence, IT consulting practices play a significant role in providing Enterprise Mobility Consultancy to turn the mobility challenges from a concern into a competitive advantage. This paper to study the successful enterprise mobility solution by examine the two IT consulting organizations and the services provided to their clients as mentioned in the literature review.